Gardienne d’un riche patrimoine archéologique : Tiaret et son précieux trésor (El Moudjahid, 2025)
Keywords: Archéologie -- Tahert

Pierre Cadenat (1902-1998) - Hadjouis, Djillali (Historiographie des préhistoriens et paléontologues d’Afrique du Nord, 2023)
Keywords: Archéologie -- Tahert; Biographies -- France

Tahart / Takdempt: archéologie - Laporte, Jean-Pierre (Encyclopédie berbère, 2025)
Keywords: Archéologie -- Tahert

An early example of glaze technology diffusion in North Africa: The Islamic workshop of Tahert (central Maghreb, Algeria) - Djellid, Akila; Pradell, Trinitat; Salinas, Elena (Journal of Archaeological Science: Reports, 2023)
A small group of ceramics from the archaeological excavations at Tahert (Algeria), the seat of the Rustamid dynasty in the 9th-early 10th centuries, has been studied for the first time by OM, SEM-EDS and micro X-ray diffraction. The ceramics belong to the earliest glazed pottery workshop found in North Africa, as other earlier or contemporary workshops in Tunisia and Egypt have not yet been found. The analysis made it possible to characterise the production of polychrome transparent lead-glazed wares, to distinguish it from other glaze workshops, and to trace links with other glaze workshops of Dar al-Islam, such as those producing ‘Raqqada Yellow’ ware. Furthermore, the polychrome glaze production of Tahert is a clear example of how migrating potters, although using the same technique, adapted to the raw materials and geographical conditions of the new area.
Keywords: Archéologie -- Tahert